2022
DOI: 10.1002/isd2.12223
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the drivers of cybersecurity enhancement in public organizations: The case of Jordan

Abstract: Electronic government systems are broadly recognized in the modern era as useful and valid means of delivering e-services. As the importance and prevalence of egovernment services have grown, increasing attention has necessarily been placed on the cybersecurity of electronic programs. Multiple drivers have been identified as contributing to the enhancement of cybersecurity, however, there is limited empirical research confirming these drivers. The main aims of this study are to investigate the drivers of e-gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Ho et al (2022) also stated that the process of technological transformation would require organizations to develop dynamic capabilities in order to align business and technical strategies and technological procedures. Al‐ma'aitah (2022) revealed that an organization's capabilities have a considerable effect on the institution's value creation. Digitizing a company's solutions can change the contribution it makes to customers by attempting to incorporate different products and services into solutions, improving products and services by adding knowledge and skills for handling consumer issues, and providing value over the lifespan of the products and services (Ross et al, 2017).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al (2022) also stated that the process of technological transformation would require organizations to develop dynamic capabilities in order to align business and technical strategies and technological procedures. Al‐ma'aitah (2022) revealed that an organization's capabilities have a considerable effect on the institution's value creation. Digitizing a company's solutions can change the contribution it makes to customers by attempting to incorporate different products and services into solutions, improving products and services by adding knowledge and skills for handling consumer issues, and providing value over the lifespan of the products and services (Ross et al, 2017).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…These deliver the strategic approach, resource assignment, and organizational culture critical to promoting a collaborative climate where innovation can flourish (Tortora et al, 2021). Al‐ma'aitah (2022) highlighted the crucial role of senior management as a vital driver in enhanced novel technological adoption, while also considering cybersecurity issues. According to Holopainen et al (2023), the managerial capabilities linked to DBS can effect digital transformation and improve collaboration capabilities by changing the organizational culture.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Governments worldwide are digitizing their operations, offering citizens a virtual portal to access various government functions (Arayankalam et al , 2021). Saudi Arabia, a prominent player in this digital revolution, has been dedicated to achieving high levels of electronic progress in e-government services (Al‐ma'aitah, 2022). The country has developed a sophisticated tapestry of electronic services and infrastructure to simplify and expedite interactions between the government and its citizens (Al‐ma'aitah, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia, a prominent player in this digital revolution, has been dedicated to achieving high levels of electronic progress in e-government services (Al‐ma'aitah, 2022). The country has developed a sophisticated tapestry of electronic services and infrastructure to simplify and expedite interactions between the government and its citizens (Al‐ma'aitah, 2022). This commitment to the digital age sets a new standard for government responsiveness and innovation.…”
Section: Introductionmentioning
confidence: 99%